2011
DOI: 10.1016/j.juro.2011.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Post-Percutaneous Nephrolithotomy Systemic Inflammatory Response: A Prospective Analysis of Preoperative Urine, Renal Pelvic Urine and Stone Cultures

Abstract: Even appropriately treated preoperative urinary infections may not prevent infected urine at percutaneous nephrolithotomy. Renal pelvic urine and stone cultures may be the only way to identify the causative organism and direct antimicrobial therapy. We recommend collecting pelvic urine and stone cultures to identify the offending organism in patients at risk for sepsis, particularly those with a large stone burden requiring multiple access tracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 19 publications
7
82
3
Order By: Relevance
“…Longer operation time contributing to the development of post-PCNL UTI has been reported by Gonen et al, 16 but other studies demonstrated that there is no statistical difference between operation time and UTI. 13,17 In our study, the operation time in patients who experienced fever attacks after tubeless PCNL was not statistically significantly longer than in patients without fever. Patients with a positive intraoperative stone culture result tended to have post-PCNL fever as reported by Gonen et al in 2008.…”
Section: Commentcontrasting
confidence: 47%
See 1 more Smart Citation
“…Longer operation time contributing to the development of post-PCNL UTI has been reported by Gonen et al, 16 but other studies demonstrated that there is no statistical difference between operation time and UTI. 13,17 In our study, the operation time in patients who experienced fever attacks after tubeless PCNL was not statistically significantly longer than in patients without fever. Patients with a positive intraoperative stone culture result tended to have post-PCNL fever as reported by Gonen et al in 2008.…”
Section: Commentcontrasting
confidence: 47%
“…Patients with a positive intraoperative stone culture result tended to have post-PCNL fever as reported by Gonen et al in 2008. 16 Lojanapiwat 17 in 2011 revealed that the collection of intraoperative pelvic urine and stone bacterial cultures is helpful for identifying the offending organism in patients at risk for sepsis. 17 Intraoperative pelvis urine culture was not routinely performed during our practice, and our data suggested that a positive stone bacterial culture result is not a contributing factor for the development of fever after tubeless PCNL.…”
Section: Commentmentioning
confidence: 99%
“…In addition, SIRS has clear specific diagnostic criteria rather than urosepsis, thence to be an important index in evaluating infection related complications in PCNL and FUL procedures. The reported incidence of SIRS after PCNL ranges form 16.7% to 23.4% [3,5], and the risk factors for SIRS following PCNL have been well evaluated in previous studies [4][5][6][7], however, the risk factors for SIRS after FUL are not well understood exactly. To our knowledge, this is the first report in literature that focuses on the post-FUL SIRS, specifically to evaluate the risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…It is previously reported by several authors that stone size, operative time, positive stone culture, positive pelvic urine culture, and multiple punctures are associated with post-PCNL infectious complications. [12][13][14][15][16] In a recent study, leukocytosis was not found to be associated with any of these predisposing factors.…”
Section: Commentmentioning
confidence: 92%